Explanation:
5x + 2x
that is the same as (5 + 2)x
and that is the same as (7)x = 7x
so, for the second part of the problem we are actually comparing
7x
and
7x - 1
there is therefore no way for the two expressions to deliver the same value for the same x.
the values of 7x are always larger by one than the values of 7x - 1
so, e.g.
x = 1
5×1 + 2×1 = 5 + 2 = 7
7×1 - 1 = 7 - 1 = 6
x = 2
5×2 + 2×2 = 10 + 4 = 14
7×2 - 1 = 14 - 1 = 13
x = 3
5×3 + 2×3 = 15 + 6 = 21
7×3 - 1 = 21 - 1 = 20
x = 4
5×4 + 2×4 = 20 + 8 = 28
7×4 - 1 = 28 - 1 = 27
x = 5
5×5 + 2×5 = 25 + 10 = 35
7×5 - 1 = 35 - 1 = 34